2017
DOI: 10.1073/pnas.1614291114
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic microtubules regulate cellular contractility during T-cell activation

Abstract: T-cell receptor (TCR) triggering and subsequent T-cell activation are essential for the adaptive immune response. Recently, multiple lines of evidence have shown that force transduction across the TCR complex is involved during TCR triggering, and that the T cell might use its force-generation machinery to probe the mechanical properties of the opposing antigen-presenting cell, giving rise to different signaling and physiological responses. Mechanistically, actin polymerization and turnover have been shown to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 82 publications
4
64
0
Order By: Relevance
“…A similar result was reported recently with a mesh format . These works were followed by many studies on lymphocyte responses to varying substrate rigidities which examine B cell activation, actin dynamics, and microtubule organizations of T cells …”
Section: Introductionsupporting
confidence: 76%
“…A similar result was reported recently with a mesh format . These works were followed by many studies on lymphocyte responses to varying substrate rigidities which examine B cell activation, actin dynamics, and microtubule organizations of T cells …”
Section: Introductionsupporting
confidence: 76%
“…[14] Complementary studies showed that T cells can apply significant traction forces to an underlying substrate through the TCR complex. [15] This suggests a feedback loop through which resistance to cell-generated forces sustains activation, allowing for rigidity sensing; in this direction, actomyosin contractility is required for a range of T cell functions including mechanosensing and overall stability of cellular interfaces. [16] Identification of the specific molecular linkages between these stages is an area of active research.…”
Section: Discussionmentioning
confidence: 99%
“…However, the contribution of the MT to force generation at the synapse has been relatively unknown, despite the fact that organelle movement as well as MT deformation clearly indicates the existence of forces. We recently found that MT tip dynamics at the lamellipodial/lamellar region modulate NMII filament assembly and lamellipodial actin flow through the RhoGTPase pathway and modulates the traction forces exerted by T cells [60]. These studies suggest that centrosomal movement and microtubule deformations result from forces generated by MT motors and the actomyosin cytoskeleton [6164], and point to the importance of interactions between the actin and MT cytoskeleton [65] in force generation and force balance at the immune synapse, but its role in TCR signaling remains to be explored.…”
Section: Cytoskeletal Dynamics During Immune Cell Activationmentioning
confidence: 99%
“…These forces were specific to TCR-ligand binding, and both actin dynamics (polymerization and depolymerization) and myosin activity were required for force generation. We have recently shown that microtubule tip dynamics modulate force generation in T cells [60]. …”
Section: Measuring Cellular Force Generation During Immune Cell Acmentioning
confidence: 99%